Comparison of Six Commercial DNA Extraction Kits for Recovery of Cytomegalovirus DNA from Spiked Human Specimens - Fahle, Gary A. (American Society for Microbiology, 2000)
We evaluated six commercially available DNA extraction kits for their ability to recover DNA from various dilutions of cytomegalovirus (CMV) added to four different specimens: bronchoalveolar lavage, cerebral spinal fluid, plasma, and whole blood. The kits evaluated included the Puregene DNA isolation kit (PG), Generation Capture Column kit, MasterPure DNA purification kit, IsoQuick nucleic acid extraction kit, QIAamp blood kit, and NucliSens isolation kit (NS). All six kits evaluated effectively removed PCR inhibitors from each of the four specimen types and produced consistently positive results down to a spiked concentration of 200 PFU of whole CMV per ml. However, the NS and PG resulted in the most consistently positive results at the lowest concentrations of spiked CMV (4 and 0.4 PFU/ml) and, in this evaluation, offered the most sensitive methods for extracting CMV DNA from the four different spiked specimens. Processing time and cost were also evaluated.